Development of a synthetic speech identification test in Kannada language - Nagaraja MN (Journal of All India Institute of Speech and Hearing, 1970)
An attempt has been made to develop ' A Synthetic Speech Identification Test In Kannada Language', to serve the urgent clinical needs on the basis of 'A new approach to speech audiometry'. Synthetic speech sentences of first and second order were construsted. They were recorded with a competing speech signal. It was presented to sixty normal ears and forty-three pathological ears. Their data were analyzed by using non-parametric statistics